Establishment of a faecal DNA quantification technique for rare and cryptic diet constituents in small mammals. (30th March 2022) - Groen, Kevin; Trimbos, Krijn B.; Hein, Susanne; Blaauw, Astrid I.; van Bodegom, Peter M.; Hahne, Joerg; Jacob, Jens
Abstract: DNA‐based approaches have greatly improved the applicability of dietary studies aimed at investigating ecological processes. These studies have provided direct insights into, otherwise difficult to measure, interactions between species and trophic levels, food web structure and ecosystem functioning. However, despite these advances, DNA‐based methods have struggled to accurately quantify the whole breadth of diet constituents because of methodological biases, such as amplification bias and digestive processes. The present study is, to our knowledge, the first diet study to use droplet digital PCR to quantify diet constituents. We manipulated the diet of wild‐caught wood mice ( Apodemus sylvaticus ) by feeding them with a known amount of small vegetable seeds (onion and carrot) and quantified the DNA traces of these diet constituents in faecal samples. The sensitivity of the technique combined with the control on the experimental design allowed mitigation of methodological bias. We were able to accurately determine DNA concentrations of small vegetable seeds in the diet of wood mice. Quantification of target DNA demonstrated significant differences in DNA content when one vs. five seeds were consumed. These differences remained significant when the age, sex and other diet constituents of the mice were altered. Different DNA markers, targeting different parts of the chloroplast, influenced onion DNA detectability. However, all onion and carrot markers showed higher DNA content for higher seed numbers. Overall, the sensitive DNA‐based approach developed in this study allows for minimally invasive quantification of small diet constituents in faeces, which would otherwise be undetectable with traditional methods.